Vesicular stomatitis virus G proteins with altered glycosylation sites display temperature-sensitive intracellular transport and are subject to aberrant intermolecular disulfide bonding - Machamer, C E; Rose, J K (The Journal of biological chemistry, 1988)
In this report we have extended our studies on a panel of vesicular stomatitis virus G proteins with altered glycosylation sites. These mutant proteins were generated by oligonucleotide-directed mutagenesis of the coding sequence to create new consensus sites for asparagine-linked oligosaccharide addition. We report that the intracellular transport of most of the mutant proteins is temperature-sensitive, implying a polypeptide folding step is affected. In addition, we find that the nonglycosylated G protein and those mutant proteins which lack oligosaccharides at the normal positions are subject to aberrant intermolecular disulfide bonding, leading to the accumulation of large complexes in the endoplasmic reticulum. These results imply that carbohydrate plays an indirect role in the intracellular transport of G protein.